Photoactivatable metabolic warheads enable precise and safe ablation of target cells in vivo - Benson, Sam; de Moliner, Fabio; Fernandez, Antonio; Kuru, Erkin; Asiimwe, Nicholas L.; Lee, Jun-Seok; Hamilton, Lloyd; Sieger, Dirk; Bravo, Isabel R.; Elliot, Abigail M.; Feng, Yi; Vendrell, Marc (Nature communications, 2021)
Photoactivatable molecules enable ablation of malignant cells under the control of light, yet current agents can be ineffective at early stages of disease when target cells are similar to healthy surrounding tissues. In this work, we describe a chemical platform based on amino-substituted benzoselenadiazoles to build photoactivatable probes that mimic native metabolites as indicators of disease onset and progression. Through a series of synthetic derivatives, we have identified the key chemical groups in the benzoselenadiazole scaffold responsible for its photodynamic activity, and subsequently designed photosensitive metabolic warheads to target cells associated with various diseases, including bacterial infections and cancer. We demonstrate that versatile benzoselenadiazole metabolites can selectively kill pathogenic cells - but not healthy cells - with high precision after exposure to non-toxic visible light, reducing any potential side effects in vivo. This chemical platform provides powerful tools to exploit cellular metabolic signatures for safer therapeutic and surgical approaches. Metabolites can distinguish pathogenic from healthy cells, but they are hard to couple to current photosensitizers without altering their biological activity. Here the authors design a new family of photosensitizers that retain metabolite function to target pathogenic cells and ablate them by photodynamic therapy.